Effect of acupuncture on decreasing blood lactate levels after exercise in elite basketball athletes - Tandya, L.; Mihardja, H.; Srilestari, A.; Kurniarobbi, J.; Kurniawan, A. (Journal of Physics: Conference Series, Volume 1073, Physics in Medical and Dental Therapy, 2018)
The study aim was to determine if acupuncture at the PC 6 Neiguan and ST 36 Zusanli points could decrease blood lactate levels in elite basketball athletes after exercise. We conducted a randomized controlled trial in 36 elite basketball athletes divided into 2 groups: the acupuncture group (n = 18) and control group (n = 18). In the acupuncture group, acupuncture was performed at the PC 6 Neiguan and ST 36 Zusanli points for 20 minutes. In the control group, no intervention was performed. Before the first session and after the twelfth, the athletes performed a specified exercise. Blood lactate levels were measured at 5 minutes and 25 minutes after exercise by using a portable blood lactate analyzer to determine the decrease due to clearance. In the acupuncture group, the decrease in blood lactate levels improved from 3.94 ± 1.11 mmol/l (study beginning) to 5.24 ± 1.22 mmol/l (study end). In the control group, the decrease in blood lactate levels improved from 3.59 ± 1.26 mmol/l (study beginning) to 3.78 ± 1.11 mmol/l (study end). The decrease in lactate levels after exercise in elite basketball athletes was significantly greater after acupuncture treatment than in the control group.